DAMPAK PROFITABILITAS DAN SOLVABILITAS PADA PROBABILITAS KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Wicaksono , Dimas Adi; Dwi Wahyuningsih , Endang; Aniqotunnafiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this research is to empirically test the effect of profitability and solvency on the timeliness of submitting financial reports. Through this research design, it is hoped that it will contribute to science, as well as practical benefits in an effort to present solutions related to the timeliness of submitting financial reports. There are 17 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 which are the locus of this research. Purposive sampling was carried out as a method of determining the sample of data and logistic regression analysis was carried out using Stata software. The findings of this study indicate that profitability and solvency have an influence on probability the timeliness of financial report submission.